Space Leaky Waves Propagating along a Pair of CRLH SIW Lines - R. Noumi; J. Machac; A. Gharsallah (Radioengineering, 2018)
A space leaky wave excited on composite right-left handed substrate integrated waveguide radiates in a wide frequency band is presented in this paper. The proposed two line array is a good candidate for smart systems of monitoring and tracking applications. The system is composed of two different lines that are placed in parallel on the same substrate. Simulation results show that the first line leaks energy in the band from 6.9 to 11 GHz with a 7.8 GHz broadside radiation frequency and the second line leaks in the band from 8.9 to 13.8 GHz; the related broadside radiation frequency is 10.2 GHz. Complex single/dual scanned beams are obtained in a wide range of angles from -72° to +73°. The simulations were carried out in the CST Microwave Studio and the obtained measurement results match well with the theoretical analysis described in this paper.